Factors Explaining Postpartum Depression among Thai Adolescent Mothers - Sunthorn, Waraphorn; Thapinta, Darawan; Panuthai, Sirirat; Xuto, Piyanut (Pacific Rim International Journal of Nursing Research, 2020)
Adolescent mothers are at risk of postpartum depression because they are presented with stressful situations due to role transition. Understanding factors explaining the stress outcomes is necessary to design effective interventions to help this group of adolescent mothers. This predictive correlational study examined whether socio-economic status, intended pregnancy, marital satisfaction, parenting stress, self-esteem, and received postpartum social support could explain postpartum depression among Thai adolescent mothers. The Stress Process Model was used as the framework for the study. Convenience sampling was used to recruit 220 adolescent mothers who attended antenatal care clinics and family planning clinics at ten hospitals in northern Thailand. Data were collected using six self-report instruments which included a Personal Information Questionnaire, the Kansas Marital Satisfaction Scale, the Parenting Stress Index-Short Form, the Rosenberg Self-esteem Scale, the postpartum Support Questionnaire, and the Edinburgh Postnatal Depression Scale. Data were analyzed using descriptive statistics and hierarchical multiple regression. Results revealed that all factors could explain only 25% of the total variance in postpartum depression among the participants. The strongest, significant factors were marital status, followed by parenting stress and self-esteem, however, socio-economic status, intentional pregnancy, and received postpartum social support did not significantly explain postpartum depression, so clearly other factors are at work. The usefulness of model outcomes in this study are therefore limited, and further development is needed including investigation of the roleof other stressors, physical causes, and postpartum symptoms. However, we emphasized that the implications for nursing practice are supported, that is to help strengthen and support the relationships of adolescent couples, promote father’s in helping to take care of children, and utilize a range of strategies to support young mothers to help reduce the potential for postpartum depression.